1986
DOI: 10.1007/bf02386810
|View full text |Cite
|
Sign up to set email alerts
|

Technetium 99m pertechnetate thyroid scintigraphy: congenital hypothyroid screening

Abstract: Technetium 99m pertechnetate thyroid scans were performed on 57 infants referred for evaluation of suspected congenital hypothyroidism. Thyroid anatomy may be characterized by four general types, based on the scintigraphic findings: (1) normal size and location; (2) ectopic location; (3) no detectable thyroid activity; (4) normal location with increased size or uptake. There are diverse etiologies of congenital hypothyroidism. Correlation of thyroid scintigraphy with blood T4 and TSH levels allows specific eti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…20 This lack of specificity of technetium Tc 99m pertechnetate may explain the low prevalence of eutopic thyroid (12%) described by Connelly et al 19 as well as other reported results of technetium Tc 99m pertechnetate scintigraphy in patients with CH. [21][22][23] The ratio of ectopic/eutopic thyroid in our series was 0.44:1 as diagnosed using 123 I scans and 1.0:1 using technetium Tc 99m pertechnetate. In the Australian series, 20 which used only technetium Tc 99m pertechnetate, the ratio was 4.4:1, ϳ9 times that of our 123 I findings (P Ͻ .001), and Ͼ4 times that of our scans using technetium Tc 99m pertechnetate (P Ͻ .01).…”
Section: Comparing Radioisotopesmentioning
confidence: 51%
“…20 This lack of specificity of technetium Tc 99m pertechnetate may explain the low prevalence of eutopic thyroid (12%) described by Connelly et al 19 as well as other reported results of technetium Tc 99m pertechnetate scintigraphy in patients with CH. [21][22][23] The ratio of ectopic/eutopic thyroid in our series was 0.44:1 as diagnosed using 123 I scans and 1.0:1 using technetium Tc 99m pertechnetate. In the Australian series, 20 which used only technetium Tc 99m pertechnetate, the ratio was 4.4:1, ϳ9 times that of our 123 I findings (P Ͻ .001), and Ͼ4 times that of our scans using technetium Tc 99m pertechnetate (P Ͻ .01).…”
Section: Comparing Radioisotopesmentioning
confidence: 51%
“…Thyroid scintigraphy ( 123 I or 99m Tc) has long been used as the method of choice for diagnostic confirmation and determination of CH aetiology in patients with clinical and laboratory evidence of this disease (Wells et al ., 1986; Verelst et al ., 1991; Sfakianakis et al ., 1999). However, the cost of this exam is relatively high, and it is not always available.…”
mentioning
confidence: 99%
“…Scintigraphy is performed rapidly, with a low radiation dose, and does not require patient preparation. Scintigraphy has been con- Fig.2a-c Case 2. a Lateral high-KV film of the neck shows anterior bowing of the trachea and thickening of the retropharyngeal soft tissues, b Noncontrast axial CT scan of the neck shows smooth extrinsic tracheal compression by a bilateral symmetric, high-density neck mass in the region of the thyroid glands, e Technetium99m pertechnetate thyroid scan shows intense uptake of radiotracer by the enlarged, slightly rounded lobes of the thyroid gland, which is in normal position sidered to be the gold standard by which the anatomical diagnosis of neonatal hypothyroidism is made [9]. Scintigraphic examination was requested by the clinical team on patient 2 to confirm that the mass seen on CT was indeed an enlarged thyroid gland (Fig.…”
Section: Discussionmentioning
confidence: 99%